Kinetics of pozzolanic reaction and carbonation in ceramic – lime system: Thermogravimetry and solid-state NMR spectroscopy study. (November 2020) - Keppert, Martin; Kobera, Libor; Scheinherrová, Lenka; Doleželová, Magdaléna; Brus, Jiří; Černý, Robert
Abstract: Waste red-clay ceramic powder (RCC) is a pozzolanic material which is currently not commercially used, but high amount of "brick fraction" of construction and demolition waste may become a source for a cheap pozzolanic additive for Portland cement and lime-based binders. A sort of specific of RCC, compared to other pozzolans, is the higher content of non-reactive minerals. Pozzolanic reaction, taking place in lime-based system, is inevitably accompanied by carbonation of the lime; these two processes are concurrent with respect to the lime consumption. Products of hydration (C–S–H and calcium aluminate hydrate phases) and carbonation (CaCO3 ) are contributing to the strengthening of the system. The goal of this research has been to evaluate the rate and mechanism of hardening of the RCC – lime mixtures. The relative rate of pozzolanic reaction and carbonation was studied over one-year period in RCC – lime pastes by help of thermal analysis and 23 Na, 27 Al and 29 Si Magic Angle Spinning Nuclear Magnetic Resonance Spectroscopy (MAS NMR), accompanied by porosimetry and compressive strength determination. The kinetics of lime conversion to hydration products and CaCO3 was determined by the help of thermogravimetry and described by Jander's equation. The highest rate of pozzolanic reaction, as well as the highest strength, reached mixture of 70% of RCC and 30% of lime; such high effective pozzolana content is caused by the phase composition of ceramic powder – it contains lower amount of reactive species, compared to metakaolin or other pozzolans. The formation of Al VI hydration products (AFm and AFt phases) took place within initial 3 days in all mixtures, while the content of C–S–H hydrates grown over the whole year of the experiment. Highlights: Hydration and carbonation were studied in ceramic – lime system by 27 Al and 29 Si MAS NMR spectroscopy and thermal analysis. Only a small amount of ceramic pozzolana added to lime caused slowdown of the lime carbonation. Formation of AFm and AFt phases took place within initial 3 days, while the content of C–S–H grown over the whole year. The highest rate of pozzolanic reaction – and strength increase – were obtained in ceramic:lime mixture 7:3.